The future of the Nile: climate change, land use, infrastructure management, and treaty negotiations in a transboundary river basin. (18th January 2017) - Barnes, Jessica
Abstract : The Nile is one of the world's major rivers; its basin is shared by 11 countries and is home to some 300 million people. This article reviews the multidisciplinary literature on the Nile to understand more about the outlook for this geopolitically significant river basin. I start by synthesizing the key results from recent climate change modeling studies, which show a warming trend for the basin, but considerable uncertainty regarding the direction of precipitation and streamflow change. I explore how different actors within the Nile Basin are perceiving and responding to climate change. Second, I look at the significance of land use, both to basin hydrology and as a driver of water demand. I highlight contemporary land use changes that could impact flows within the Nile Basin. Third, I examine the role of infrastructure in influencing the magnitude and temporality of flows along the river. I focus, in particular, on the Grand Ethiopian Renaissance Dam, its projected impacts, and the concerns it has generated. Finally I explore the geopolitical context of the basin, and the ongoing conflict over water sharing agreements. I look at the treaty currently on the table, the Cooperative Framework Agreement, and the political issues it has raised. In bringing together this diverse literature, the article offers a timely and multifaceted insight into the varied factors that will shape the future of the Nile. WIREs Clim Change 2017, 8:e449. doi: 10.1002/wcc.449 This article is categorized under: Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change Trans‐Disciplinary Perspectives > Regional Reviews Abstract : The Nile, Aswan, Egypt. Photo by Jessica Barnes.